Coupling in thermo-mechanical wave propagation in NaF at low temperature - Frischmuth, K.; Cimmelli, V.A. (Archives of Mechanics, 1998)
In the present paper we consider a linearly elastic heat conductor for which the semi-empirical heat transfer model [7] is assumed. Material functions are defined in accordance with measured parameters for NaF at 15 K. At that temperature, first and second sound waves have been observed in experiments. Both waves are reproduced by our coupled thereto-mechanical model.